Synergistic cytotoxicity from combination of imatinib and platinum-based anticancer drugs specifically in Bcr-Abl positive leukemia cells - Yuming Wei; Kenneth K.W. To; Steve C.F. Au-Yeung (Elsevier, 2015)
Imatinib, a multitargeted tyrosine kinase inhibitor, exhibits potent anticancer activity against leukemia harboring the Bcr-Abl oncogene and some solid tumors overexpressing c-kit and PDGFR. However, its clinical efficacy is severely compromised by the emergence of resistance primarily due to acquired mutations in the Bcr-Abl kinase domain. In this study, we showed that combination of imatinib with platinum (Pt)-based anticancer agents, including cisplatin and oxaliplatin, exhibited synergistic cytotoxic effect specifically in Bcr-Abl+ human chronic myeloid leukemia cell line K562 but not in Bcr-Abl− RPMI8226 cells. Importantly, the synergistic effect was also found to circumvent imatinib resistance in an imatinib-selected resistant subline K562 ima1.0. The combination treatment increased apoptosis and DNA damage. Mechanistic study revealed that increased inhibition of Bcr-Abl and downstream ERK phosphorylation by the drug combination may contribute to the synergistic effect.